Wearable motion sensors and digital biomarkers in stroke rehabilitation - Derungs, Adrian; Schuster-Amft, Corina; Amft, Oliver (Current Directions in Biomedical Engineering, 2020)
We propose three novel digital biomarkers for the longitudinal performance monitoring and movement evaluation of hemiparetic patients, e.g. after stroke. We devised convergence points (CP) for the bilateral walking analysis based on gait parameters, e.g. stride duration using regression- modelling to estimate similarity between body sides. The physical activity (PA) was devised to evaluate the energy expenditure of all extremities during training and free-living. The functional range of motion (fROM) is a digital biomarker to quantify the upper arm reaching ability, represented in 3D visualisations. In this work, we detail CP, PA, and fROM to derive rehabilitation insights for personalising therapies. We evaluated the proposed digital biomarkers in a clinical observation study with 11 patients after stroke during their rehabilitation including therapy and self-paced daily routines.
CRIS-Team Scopus Importer:2020-12-18
Keywords: digital twin; free-living; gait analysis; gait parameter; hemiparesis; Inertial measurement unit; stroke